MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE JARIMATIKA PADA SISWA KELAS II SD NEGERI 005 KEPENUHAN T.P 2017/2018 - Asyiah Asyiah (Indonesian Journal of Basic Education, 2018)
Mathematical learning material for addition and reduction in numbers of students experiences a decrease in interest in these subjects. This is because students' understanding of the material is very low. This study aims to improve student learning outcomes in solving students' mathematical problems on the subject of addition and subtraction of class II SDN 005 Fullness. The purpose of this study was also to find out the results of learning mathematics using the Jarimatika method. Based on the results of the study it can be concluded that the Jarimatika learning method can improve the ability and results of mathematics learning in class II SDN 005 students. This is indicated by an increase in the class average value, which is at the time of cycle 62.96 to 72.59 in the first cycle and 82.86 in the second cycle. The application of the use of the method Jarimatika managed to improve the mastery of the material and student learning outcomes in mathematics learning